2013
DOI: 10.1017/s1041610213001932
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term neurocognitive functioning after electroconvulsive therapy in depressed elderly: a prospective naturalistic study

Abstract: In our severely depressed elderly patients, neurocognitive performance improved or did not change after ECT. Patients with poor cognitive function were not able to participate in neuropsychological assessment before ECT started. Consequently these results may not apply to patients with more severe cognitive impairment prior to the start of ECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 35 publications
9
32
2
Order By: Relevance
“…Our finding is consistent with previous findings obtained for younger adults (McClintock et al, 2014;Semkovska & McLoughlin, 2010) and adds important information to the few studies performed in the elderly (Gardner & O'Connor, 2008;Verwijk et al, 2014). The finding that retrograde amnesia for public facts was not evident at T3 is consistent with results of several (Meeter, Murre, Janssen, Birkenhager, & van den Broek, 2011), but not all (Lisanby et al, 2000), previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our finding is consistent with previous findings obtained for younger adults (McClintock et al, 2014;Semkovska & McLoughlin, 2010) and adds important information to the few studies performed in the elderly (Gardner & O'Connor, 2008;Verwijk et al, 2014). The finding that retrograde amnesia for public facts was not evident at T3 is consistent with results of several (Meeter, Murre, Janssen, Birkenhager, & van den Broek, 2011), but not all (Lisanby et al, 2000), previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…The comparison of group means revealed the absence of side effects of ECT, with the exception of declined phonemic verbal fluency. This finding was in accordance with the results of Verwijk et al (2014); these authors found no indications of cognitive side effects both within one week after ECT and six months later. However, group data might conceal cognitive side effects of ECT in a subgroup of elderly patients .…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Verwijk et al [58] assessed cognition before and after age-formula-dosed, brief pulse ECT (RUL, BL) in both unipolar and bipolar depressed elderly participants (≥55 years, range . Improvements in global cognition and memory, and no changes in measures which assessed attention and executive function were reported after ECT.…”
Section: Ect and Cognition In The Elderlymentioning
confidence: 99%